The Free Womb Law and the administration of historical time in Imperial Brazil - Miranda, Bruno (Anais do Museu Paulista: História e Cultura Material, 2023)
This article seeks to understand the Free Womb Law by analyzing the historical time. It argues that the Law of September 28, 1871, was, in its long gestation processes, conceived as an instrument to control the time of Brazilian emancipation, guiding its rhythm, intensity, and duration. The analysis will be based in the debates of the Council of State of 1867 and 1868, in the parliamentary debates of 1870 and 1871, in the press discussions of 1871 and in an engraving that commemorated the freedom of the womb as soon as it was approved.